ОЦІНЮВАННЯ ЕФЕКТИВНОСТІ РОБОТИ МАЛОГО МОДУЛЬНОГО ЯДЕРНОГО РЕАКТОРА НА РИНКУ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Є.В. Парус; І.В. Блінов; А.О. Костіков (Праці Інституту електродинаміки Національної академії наук України)
A mathematical model for constructing an optimal loading schedule of a power unit with a small modular nuclear reac-tor is presented. The main conditions of operation of small modular nuclear reactors with constructive solutions similar to the development of NuScale are determined, and the architecture of the mathematical model for the search of optimal schedules of their operation is presented. The main attributes of the operating modes of small modular nuclear reactors and a mathematical model for simulating the control functions of the reactor operation schedules have been deter-mined. The main components for displaying the results of purchase-lease/sale of electricity by the power-generating company have been determined. The objective function of maximizing the benefit from the operation of a small modular nuclear reactor and limiting the profitability of its operation is given. The basics of the methodology of using the model for building the optimal daily schedule of the functioning of a small modular nuclear reactor in the tasks of assessing the effect of the construction and operation of such reactors at a nuclear power plant have been formulated. Ref. 15, fig. 4, table.